Inequidades en salud relacionadas con el VIH/SIDA (2009)
ABSTRACT: There are three theories that could explain the origin of health inequities between population groups. These theories integrated proximal and distal social factors, so-called social determinants on health, which are related to the causes of diseases. The main purpose of this article is to review and analyze some reflections and published papers about social determinants of HIV-AIDS in order to identify some issues related to the pandemic in Colombia.